Transboundary air pollution and cross-border cooperation: Insights from marine vessel emissions regulations in Hong Kong and Shenzhen - KIM, Seung Kyum (Institutional Knowledge at Singapore Management University, 2022)
Many coastal cities regulate shipping emissions within their jurisdictions. However, the transboundary nature of air pollution makes such efforts largely ineffective unless they are accompanied by reciprocal, legally-binding regulatory agreements with neighbouring cities. Due to various technical, economic, and institutional barriers, it has thus far been difficult to isolate the effects of legally-binding cross-border cooperation on vessel emissions at the city-level. We exploit the unique administrative characteristics of Hong Kong and its relationship with neighbouring cities in China's Pearl River Delta to isolate the effect of legally-binding cross-border cooperation. Using a regression discontinuity design, we find that Hong Kong's unilateral implementation of marine vessel fuel control policy left the city exposed to SO2 from marine vessel emissions originating in Shenzhen. Only when Shenzhen implemented its own legally binding policy did such pollution in Hong Kong reduce significantly across all seasons. While international agreements on air pollution are important, they face well-known difficulties related to scale and multilateral complexity. Our findings therefore suggest that contiguous cities—whether or not they straddle an international border—can play an important role in the timely development of effective emissions standards.